Genome-Centric Analysis of a Thermophilic and Cellulolytic Bacterial Consortium Derived from Composting - Lemos, Leandro N.; Pereira, Roberta V.; Quaggio, Ronaldo B.; Martins, Layla F.; Moura, Livia M. S.; da Silva, Amanda R.; Antunes, Luciana P.; da Silva, Aline M.; Setubal, João C. (Frontiers in Microbiology, 2017)
Microbial consortia selected from complex lignocellulolytic microbial communities are promising alternatives to deconstruct plant waste, since synergistic action of different enzymes is required for full degradation of plant biomass in biorefining applications. Culture enrichment also facilitates the study of interactions among consortium members, and can be a good source of novel microbial species. Here we used a sample from a plant waste composting operation in the São Paulo Zoo (Brazil) as inoculum to obtain a thermophilic aerobic consortium enriched through multiple passages at 60°C in carboxymethylcellulose as sole carbon source. The microbial community composition of this consortium was investigated by shotgun metagenomics and genome-centric analysis. Six near-complete (over 90%) genomes were reconstructed. Similarity and phylogenetic analyses show that four of these six genomes are novel, with the following hypothesized identifications: a new Thermobacillus species; the first Bacillus thermozeamaize genome (for which currently only 16S sequences are available) or else the first representative of a new family in the Bacillales order; the first representative of a new genus in the Paenibacillaceae family; and the first representative of a new deep-branching family in the Clostridia class. The reconstructed genomes from known species were identified as Geobacillus thermoglucosidasius and Caldibacillus debilis. The metabolic potential of these recovered genomes based on COG and CAZy analyses show that these genomes encode several glycoside hydrolases (GHs) as well as other genes related to lignocellulose breakdown. The new Thermobacillus species stands out for being the richest in diversity and abundance of GHs, possessing the greatest potential for biomass degradation among the six recovered genomes. We also investigated the presence and activity of the organisms corresponding to these genomes in the composting operation from which the consortium was built, using compost metagenome and metatranscriptome datasets generated in a previous study. We obtained strong evidence that five of the six recovered genomes are indeed present and active in that composting process. We have thus discovered three (perhaps four) new thermophillic bacterial species that add to the increasing repertoire of known lignocellulose degraders, whose biotechnological potential can now be investigated in further studies.